5mC and H3K9me3 of TRAF3IP2 promoter region accelerates the progression of translocation renal cell carcinoma - Lei Yang; Yi Chen; Ning Liu; Yanwen Lu; Xin Li; Wenliang Ma; Weidong Gan; Dongmei Li (Biomarker Research, 2022)
Abstract Background In our previous study, we found that lncRNA TRAF3IP2 antisense RNA 1 (TRAF3IP2-AS1) could play a critical role in the progression of NONO-TFE3 translocation renal cell carcinoma (NONO-TFE3 tRCC). However, the function of TRAF3IP2 (TRAF3 interacting protein 2), encoded by the complementary strand of TRAF3IP2-AS1, remains poorly understood in NONO-TFE3 tRCC. Methods Immunohistochemistry, western blot, and qRT-PCR were undertaken to study the expression and clinical significance of TRAF3IP2 in Xp11.2 tRCC tissues and cells. The functions of TRAF3IP2 in tRCC were investigated by proliferation analysis, EdU staining, colony and sphere formation assay, Transwell assay, and apoptosis analysis. The regulatory mechanisms among TRAF3IP2, NOTCH1, and TRAF3IP2-AS1 were investigated by luciferase assay, RNA immunoprecipitation, western blot, methylated DNA Immunoprecipitation, and CRISPR/dCas9-based system. Results The results showed that TRAF3IP2 was highly expressed in NONO-TFE3 tRCC tissues and cells, and the silence of TRAF3IP2 inhibited the proliferation, migration, and invasion of UOK109 cells which were derived from cancer tissue of patient with NONO-TFE3 tRCC. Mechanistic studies revealed that TRAF3IP2 functioned as a co-activator of NOTCH1 to activate the NOTCH1 pathway. Meanwhile, HNRNPK, DNMT1 and SETDB1 could be recruited by TRAF3IP2-AS1 to the promoter region of TRAF3IP2, which mediated 5-hydroxymethylcytosine (5mC) on DNA and trimethylated lysine 9 of histone H3 (H3K9me3) at transcriptional level to repress the expression of TRAF3IP2. Conclusions TRAF3IP2 functions as an oncogene in NONO-TFE3 tRCC progression and might serve as a novel target for NONO-TFE3 tRCC therapy.